Inspiracje patrystyczne w refleksji nad postępowaniem terapeutycznym - Amilkiewicz-Marek, Agnieszka; Wysocki, Marcin (Vox Patrum, 2025)
The article addresses the problem of understanding the concepts of therapy and therapist within the context of patristic thought and their relevance to contemporary speech therapy practice. The study adopts a hermeneutic and comparative approach, analyzing selected writings of the Church Fathers – especially Basil the Great, Gregory of Nazianzus, John Chrysostom, Augustine, Clement of Alexandria, and Paulinus of Nola – to explore the spiritual and moral dimensions of healing and human formation and the importance of the word in this process. The structure of the article moves from the exegesis of patristic sources, through a comparison with modern therapeutic principles, to the formulation of guidelines inspired by Christian tradition. Using historical-theological content analysis, the author demonstrates that, in patristic anthropology, therapy signifies the healing of the soul through word, relationship, and love. The findings highlight the enduring contribution of patristic thought to the anthropological and ethical foundations of contemporary speech therapy, revealing it as a form of service and integral accompaniment of the human person in their process of growth and restoration.